On the deposits of the Black Sea. - Murray, John (PANGAEA, 1900)
Professor N. Andrussow, of Juriew (Dorpat) sent to the author a series of the deposit-samples collected in the Black Sea during the Russian explorations in 1890 and 1891 in the steamships Tschernomoretz, Zaporojetz, and Donetz. These deposits were submitted to careful microscopical examination and chemical analysis.
Annotated record of the detailed examination of Mn deposits from the SS Tschernomoretz expedition in the Black Sea in 1890-1891
Keywords: Black Sea; Comment; Deposit type; DEPTH, sediment/rock; Description; Dredge; DRG; NOAA and MMS Marine Minerals Geochemical Database; NOAA-MMS; Page(s); Position; Quantity of deposit; Sample code/label; Sample ID; Sediment type; Size; Substrate type; TSCHNM-15; TSCHNM-2; TSCHNM-3; TSCHNM-50; TSCHNM-51; TSCHNM-52; TSCHNM-55